2017
DOI: 10.1038/s41598-017-03971-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary mastic oil extracted from Pistacia lentiscus var. chia suppresses tumor growth in experimental colon cancer models

Abstract: Plant-derived bioactive compounds attract considerable interest as potential chemopreventive anticancer agents. We analyzed the volatile dietary phytochemicals (terpenes) present in mastic oil extracted from the resin of Pistacia lentiscus var. chia and comparatively investigated their effects on colon carcinoma proliferation, a) in vitro against colon cancer cell lines and b) in vivo on tumor growth in mice following oral administration. Mastic oil inhibited -more effectively than its major constituentsprolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 44 publications
5
55
0
1
Order By: Relevance
“…Previous in vitro and in vivo studies have examined the antioxidant, anti-inflammatory, and anti-apoptotic potential of pistachio [21,[34][35][36][37][38]. In particular, the pistachio properties were tested on carrageenan or LPS-induced acute inflammatory response [39,40], inflammatory bowel disease, colitis [24,[41][42][43], cancer [44][45][46], and allergic inflammation in the asthmatic model [47]. To our knowledge, the present study was the first to explore the anti-inflammatory effects of pistachios in mice with HFD-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have examined the antioxidant, anti-inflammatory, and anti-apoptotic potential of pistachio [21,[34][35][36][37][38]. In particular, the pistachio properties were tested on carrageenan or LPS-induced acute inflammatory response [39,40], inflammatory bowel disease, colitis [24,[41][42][43], cancer [44][45][46], and allergic inflammation in the asthmatic model [47]. To our knowledge, the present study was the first to explore the anti-inflammatory effects of pistachios in mice with HFD-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are several studies regarding the beneficial effects of pistachio. In particular, there are studies on carrageenan or LPS-induced acute inflammatory response [ 4 , 16 ], inflammatory bowel disease and colitis [ 21 , 35 , 36 , 37 ], cancer [ 38 , 39 , 40 ], allergic inflammation in asthmatic model [ 41 ] and many other experimental models. Furthermore, the antimicrobial properties of polyphenolic fractions obtained from natural raw and roasted salted pistachios have also been evaluated [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myrcene was the second abundant component in the C. citratus essential oils. However, previous studies indicated that this compound exhibited weak cytotoxicity against different cancer cell lines [22][23][24]. e third abundant compound, geraniol, has been reported to display significant anticancer activity via different signaling pathways [25,26].…”
Section: Investigation On the Mechanism Of Action Of Lemongrassmentioning
confidence: 98%